2022
DOI: 10.1002/cctc.202101969
|View full text |Cite
|
Sign up to set email alerts
|

Elucidating Ru Distribution State of Ru‐Promoted Pr2Sn2O7 Pyrochlore and its Effect on the Catalytic Performance for Toluene Deep Oxidation

Abstract: 4 + . The distribution states of Ru affect significantly the active surface oxygen amount and the toluene adsorption capacity, which are the two major reasons influencing the reactivity. On Ru/ Pr 2 Sn 2 O 7 , a greater quantity of active oxygen sites can be formed than on RuÀ Pr 2 Sn 2 O 7 . Furthermore, the presence of surface Ru 0 facilitates also toluene adsorption. As a consequence, the intrinsic activity of the two Ru/Pr 2 Sn 2 O 7 catalysts are much higher than the two RuÀ Pr 2 Sn 2 O 7 catalysts . It i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 54 publications
0
4
0
Order By: Relevance
“…The former is assigned to the surface superoxide anions (O 2 − ), and the latter is ascribed to the surface oxygen species defined as O δ − (0 < δ < 1). 49,50 After 5 minutes, the two peaks reached a steady state, proving that the surface was fully oxidized by O 2 . After a duration of 20 minutes, a feed consisting of 10% H 2 /Ar was introduced into the cell while maintaining the same temperature.…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…The former is assigned to the surface superoxide anions (O 2 − ), and the latter is ascribed to the surface oxygen species defined as O δ − (0 < δ < 1). 49,50 After 5 minutes, the two peaks reached a steady state, proving that the surface was fully oxidized by O 2 . After a duration of 20 minutes, a feed consisting of 10% H 2 /Ar was introduced into the cell while maintaining the same temperature.…”
Section: Resultsmentioning
confidence: 94%
“…S1 (ESI†) can be categorized into two groups: one group, denoted as α type, occurs in the temperature range of 50–200 °C and corresponds to the release of loosely bonded surface oxygen; 24,49 while the other group, referred as β type, appears between 200 and 700 °C and is associated with the release of surface lattice O 2− . 24,49 As quantified in Table 3, the integrated areas of the α peak for Cr–SnO 2 and Nb–SnO 2 show significant improvement, indicating the presence of a larger amount of surface facile oxygen compared to individual SnO 2 . For Li–SnO 2 and Mg–SnO 2 , the amount of this part of oxygen species becomes smaller.…”
Section: Resultsmentioning
confidence: 99%
“…After the introduction of the Ru species, the two new peaks can be observed at 564 and 1090 cm −1 , which are assigned to 3-fold rings and vibrational modes involving SiO 4 units, respectively [31,32]. The weak peak at 323 cm −1 can be detected, which can be assigned to RuO 2 species [33]. UV-Vis spectra profiles are shown in Figure S3.…”
Section: Structural Propertiesmentioning
confidence: 95%
“…Over past 12 years, with the objective to understand the catalytic chemistry of A 2 B 2 O 7 compounds, our group has purposely designed and fabricated a bunch of samples with varied A- and B-site combinations and used for different reactions, such as CO oxidation, VOCs and soot particulate combustion, CH 4 reforming, and oxidative coupling of CH 4 . Through designing La 2 B 2 O 7 catalysts with different B-sites (B = Ti 4+ , Zr 4+ , and Ce 4+ ), it has been revealed that different fine crystalline phases can be formed. The La 2 Ce 2 O 7 catalyst with a disordered defect fluorite phase possesses the largest amount of OCM reactive/selective oxygen sites (O 2 – ), hence demonstrating the best reaction performance.…”
Section: Introductionmentioning
confidence: 99%